2023
DOI: 10.3390/jfb14030159
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Materials for Tissue Engineering: Development, Classification and Current Applications

Abstract: The goal of this review is to map the current state of biodegradable materials that are used in tissue engineering for a variety of applications. At the beginning, the paper briefly identifies typical clinical indications in orthopedics for the use of biodegradable implants. Subsequently, the most frequent groups of biodegradable materials are identified, classified, and analyzed. To this end, a bibliometric analysis was applied to evaluate the evolution of the scientific literature in selected topics of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 141 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…Titanium biomaterials are still widely used for the manufacture of implants. Provided they are properly processed, they enable reliable long-term implant performance even in stressful situations [1,9]. Wang et al in his work pointed out scaffolds made of titanium and its alloys as suitable for the production of implants and the repair of bone defects, used primarily in orthopedics, due to their advanced mechanical properties, corrosion resistance and favorable osseointegration [2].…”
Section: Discussionmentioning
confidence: 99%
“…Titanium biomaterials are still widely used for the manufacture of implants. Provided they are properly processed, they enable reliable long-term implant performance even in stressful situations [1,9]. Wang et al in his work pointed out scaffolds made of titanium and its alloys as suitable for the production of implants and the repair of bone defects, used primarily in orthopedics, due to their advanced mechanical properties, corrosion resistance and favorable osseointegration [2].…”
Section: Discussionmentioning
confidence: 99%
“…The process of degradation and he longevity of a scaffold material in the biological system are key factors in selecting the biomaterial therapeutics [33]. The process of degradation can be hydrolysis and or enzymatic, and the resulting degraded products should be non-immunogenic and non-toxic and are incorporated into metabolic pathways or excreted [34].…”
Section: Biodegradabilitymentioning
confidence: 99%
“…Accordingly, it is important to choose materials with the ability to suppress excessive inflammation [ 165 ]. Furthermore, efforts have been made to design biodegradable polymers that selectively activate the M2 phenotype of macrophages [ 166 ]. In order to drive primary human macrophage elongation and differentiation towards the anti-inflammatory, pro-healing M2 type, a previous study showed that the control of biomaterial geometry using melt electrowriting to create fibrous scaffolds with box-shaped pores and inter-fiber spacing can potentially enhance tissue regeneration [ 167 ].…”
Section: Mechanisms Of Host-biomaterials Interactionmentioning
confidence: 99%